Penerapan Insinerator Sampah Sederhana dalam Mengatasi Masalah Penumpukan Sampah di Desa Sariwangi - Defrianto Pratama; Rahmawati Hasanah; Yunita Citra Dewi; Destri Muliastri; Devi Eka Septiyani Arifin; Zainuddin Zainuddin; Sri Widarti; Muhammad Rizki Zuhri; Ajeng Ayu Milanti (Politeknik Kampar, 2025)
Waste management is a major issue in Sariwangi Village, West Bandung Regency, due to the lack of public knowledge, skills, and awareness regarding technology-based waste processing. This problem is exacerbated by inadequate equipment and low community participation. To address these challenges, an incineration method was introduced through a community service program involving problem identification, literature review, awareness campaigns, waste separation, provision of equipment, and training on the use of waste processing technology. The program also developed strategies to enhance community involvement in waste management. The expected outcomes include improved knowledge and skills, availability of proper equipment, and increased awareness and participation in maintaining environmental cleanliness. This approach aims to create a cleaner, healthier, and more sustainable village environment. Keywords: Waste management; Incineration technology; Incinerator